Gender-based violence, religion and forced displacement: Protective and risk factors - Pertek, Sandra; Block, Karen; Goodson, Lisa; Hassan, Pakinam; Hourani, Jeanine; Phillimore, Jenny (Frontiers in Human Dynamics, 2023)
Introduction This paper examines the relationship between gender-based violence (GBV) and religion in a range of forced displacement contexts. While it has been acknowledged that religion frequently shapes experiences of GBV survivors, little is known about the influences of religion on GBV experiences in forced displacement and its potential role in strengthening interventions. Methods Utilizing empirical evidence from 58 interviews from the SEREDA project with forced migrants in Sweden, UK, Turkey and Australia, we outline the interactions between religious resources and GBV in migrants' forced displacement experiences. We conceptualise religious resources as comprising religious ideas, religious practices, religious experience and religious organization. Results Survivors talked about religion spontaneously when responding to questions relating to resilience, coping mechanisms, and risk factors. Religion acted as both a “protective” and “risk” factor for GBV experiences. Religious beliefs were assets in coping with GBV experiences, but also contributed to creating an environment in which violence was normalized, exposing women to further harm. Religious practices supported survivors emotionally to cope with GBV but also some practices posed risks. Religious organizations in many cases served as a lifeline for many displaced women, offering practical and emotional support, however religious leaders at times encouraged survivors to stay in abusive relationships. Religious experiences “empowered” and “disempowered” survivors across the processes of forced migration. Discussion We demonstrate the relevance and importance of acknowledging the role of religion in the experiences of GBV in forced displacement. Our analysis advances the understanding of religious resources as both protective and risk factors that affect forced migrants' experiences of GBV over time and place. We suggest a way forward for practitioners and researchers to account for the roles of religion in experiences of GBV and forced displacement, as opportunities and barriers to GBV prevention and response, and to work with religious leaders and local faith communities to strengthen protection of survivors.